(untitled) (Journal of Rashid Latif Medical College, 2025)
Background: Mobile phone addiction and academic procrastination are common challenges among medical students, negatively influencing academic outcomes. Objective: This study explored the influence of demographic factors on mobile phone addiction, academic procrastination, and academic achievement among Pakistani medical students, and examined the association between these variables. Methodology: A cross-sectional study was conducted at University College of Medicine & Dentistry, Lahore, between May and June 2024. A total of 3,511 medical students completed an online questionnaire (response rate = 81.7%). Instruments included a demographic survey, the Scale of Academic Achievement, Mobile Phone Problem Use Scale (MPPUS-10), and Academic Procrastination Scale–Short (APS-S). Data were analyzed using variance analysis and hierarchical regression. Results: Mean scores were: academic procrastination 2.66 ± 0.91, mobile phone addiction 5.13 ± 1.53, and academic achievement 4.51 ± 0.71. Gender, study year, leadership experience, and family income showed significant differences. Mobile phone addiction was negatively associated with learning dedication, learning performance, and relationship facilitation. Academic procrastination was negatively related to learning dedication, learning performance, relationship facilitation, and objective achievement. Conclusion: Mobile phone addiction and academic procrastination are prevalent among Pakistani medical students at University College of Medicine & Dentistry, Lahore with significant negative impacts on academic achievement. Institutional strategies are needed to mitigate these behaviors.